Water, chores (faenas) and communal organization: San Pedro de Casta - Huarochirí - Gelles, Paul H. (1984)
The important role that water management has played in social organization and in the formation of so-called "hydraulic societies" is an issue that has interested many social scientists. The following article, which focuses on communal work, demonstrates the importance of water in the social organization of an Andean peasant community. The author is a postgraduate student of Anthropology at the Pontifical Catholic University. This article is part of a thesis prepared at the Post-Graduate of the Pontifical Catholic University.